Revisiting 5G quality of service in Bangkok metropolitan region: BTS Skytrain station areas - Daengsi, Therdpong; Sriamorntrakul, Pakkasit; Chatchalermpun, Surachai; Phanrattanachai, Kritphon (Institute of Advanced Engineering and Science, 2024)
This article compares two of the leading mobile network operators (MNOs) in Thailand’s telecom market in terms of the service quality of Thailand’s fifth generation (5G) networks. The following three factors: download speed, upload speed, and latency, which are frequently considered to be indicators of the quality of Internet networks, were examined. The researchers employed the test results to determine the quality of service (QoS) that was achieved by comparing newly collected data to data that had previously been examined utilizing the same format and application in the middle of May 2021. The average download speed decreased from 196.4 Mbps in 2021 to 140.4 Mbps in 2023, while the average upload speed dropped from 62.6 Mbps in 2021 to 52.0 Mbps in 2023. Furthermore, the average latency increased from 14.9 ms in 2021 to 23.3 ms in 2023. These results show a considerably enhanced service although the test region in this study only comprised BTS stations. Furthermore, this was the case even though the test area in this study only encompassed a small percentage of the total population.